PROFESIONALISME PENDIDIK MENGGUNAKAN BAHASA INGGRIS DALAM PROSES TEACHING-LEARNING SAAT PELATIHAN DI BDK MAKASSAR - Hanafi Pelu (Nizamia Learning Center, 2021)
A language is a tool of communication. English is an international language in the world. Education training place is a place to civil servants follows training, which handles by educators in that place whereas following by adults people especially for Religious Ministary Affairs. So, when training in the process, educators professionalism is very important to delivered the materials for the participants and all the elements are using language, but especially for educators when they using English. A language is a tool of communication, how far our understanding in English, and how far we can use it.